2018
DOI: 10.1016/j.freeradbiomed.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Redox and the circadian clock in plant immunity: A balancing act

Abstract: Plants’ reliance on sunlight for energy makes their light-driven circadian clock a critical regulator in balancing the energy needs for vital activities such as growth and defense. Recent studies show that the circadian clock acts as a strategic planner to prime active defense responses towards the morning or daytime when conditions, such as the opening of stomata required for photosynthesis, are favorable for attackers. Execution of the defense response, on the other hand, is determined according to the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 87 publications
3
51
0
Order By: Relevance
“…2017; Karapetyan & Dong, 2018). As a redox-sensitive immune regulator, NPR1 links changes in cellular redox states to immune activation and also clock regulation under light-dark cycling.…”
Section: Circadian Clockmentioning
confidence: 99%
“…2017; Karapetyan & Dong, 2018). As a redox-sensitive immune regulator, NPR1 links changes in cellular redox states to immune activation and also clock regulation under light-dark cycling.…”
Section: Circadian Clockmentioning
confidence: 99%
“…Our results also demonstrated that CHT significantly caused stomatal closure before dark/light transition only if the elicitor treatment was carried out in the previous light phase of the day (at 17:00 hrs). This response of plants upon CHT treatment could be substantial, because stomata must be opened at dawn (dark/light transition) to facilitate photosynthetic CO 2 assimilation but they provide also infection window for some pathogens [21]. Not only the dark/light transition but also the first part of the light period can influence and determine the plant defence responses in different ways.…”
Section: Daytime and Light Dependency Of Stomatal Responsementioning
confidence: 99%
“…In the morning, the core circadian clock component CCA1 regulates the expression of several defence genes, such as catalases to manage ROS homeostasis and to affect defence responses through redox changes [40]. At 09:00 hrs, when the expression of defence genes shows a peak [21], stomata were closed in case of leaves treated in the morning (at 08:00 hrs) and at dawn (at 04:00 hrs).…”
Section: Daytime and Light Dependency Of Stomatal Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Within these cycles, light causes the accumulation of reactive oxygen species (ROS) (Pitzschke et al, 2006), while pathogen invasion is often favored at a given time of day (Shin et al, 2012;Korneli et al, 2014;Karapetyan and Dong, 2018;Li et al, 2018;Zhang et al, 2019). These perturbations often elicit various types of oxidative bursts (Karapetyan and Dong, 2018;Zhang et al, 2019). Given the predictable, timed nature of these abiotic and biotic stressors, the plant circadian clock provides timed sensitivity resistance to such agents.…”
Section: Introductionmentioning
confidence: 99%